Lesbian and bisexual women's likelihood of becoming pregnant: a systematic review and meta‐analysis. (15th December 2016) - Hodson, K; Meads, C; Bewley, S
Abstract : Background: Few data exist regarding pregnancy in lesbian and bisexual (LB) women. Objectives: To determine the likelihood of LB women becoming pregnant, naturally or assisted, in comparison with heterosexual women Search strategy: Systematic review of papers published 1 January 2000 to 23 June 2015. Selection criteria: Studies contained details of pregnancy rates among LB women compared with heterosexual women. No restriction on study design. Data collection and analysis: Inclusion decisions, data extraction and quality assessment were conducted in duplicate. Meta‐analyses were carried out, with subgroups as appropriate. Main results: Of 6859 papers identified, 104 full‐text articles were requested, 30 papers (28 studies) were included. The odds ratio (OR) of ever being pregnant was 0.19 (95% CI 0.18–0.21) in lesbian women and 1.22 (95% CI 1.15–1.29) in bisexual women compared with heterosexual women. In the general population, the odds ratio for pregnancy was nine‐fold lower among lesbian women and over two‐fold lower among bisexual women (0.12 [95% CI 0.12–0.13] and 0.50 [95% CI 0.45–0.55], respectively). Odds ratios for pregnancy were higher for both LB adolescents (1.37 [95% CI 1.18–1.59] and 1.98 [95% CI 1.85, 2.13], respectively). There were inconsistent results regarding abortion rates. Lower rates of previous pregnancies were found in lesbian women undergoing artificial insemination (OR 0.17 [95% CI 0.11–0.26]) but there were higher assisted reproduction success rates compared with heterosexual women (OR 1.56 [95% CI 1.24–1.96]). Conclusions: Heterosexuality must not be assumed in adolescents, as LB adolescents are at greater risk of unwanted pregnancies and terminations. Clinicians should provide appropriate information to all women, without assumptions about LB patients' desire for, or rejection of, fertility and childbearing. Tweetable abstract: Review of likelihood of LB women becoming pregnant: LB teenagers at greater risk of unwanted pregnancies. Abstract : Tweetable abstract Review of likelihood of LB women becoming pregnant: LB teenagers at greater risk of unwanted pregnancies. This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights14414 .